The tellurium-based immunomodulator, AS101 ameliorates adjuvant-induced arthritis in rats. (8th December 2020) - Halpert, G; Halperin Sheinfeld, M; Monteran, L; Sharif, K; Volkov, A; Nadler, R; Schlesinger, A; Barshak, I; Kalechman, Y; Blank, M; Shoenfeld, Y; Amital, H
Summary: Despite undeniable improvement in the management of rheumatoid arthritis (RA), the discovery of more effective, less toxic and, ideally, less immune suppressive drugs are much needed. In the current study, we set to explore the potential anti-rheumatic activity of the non-toxic, tellurium-based immunomodulator, AS101 in an experimental animal model of RA. The effect of AS101 was assessed on adjuvant-induced arthritis (AIA) rats. Clinical signs of arthritis were assessed. Histopathological examination was used to assess inflammation, synovial changes and tissue lesions. Very late antigen-4 (VLA-4) + cellular infiltration was detected using immunohistochemical staining. Enzyme-linked immunosorbent assay (ELISA) was used to measure circulating anti-cyclic citrullinated-peptide autoantibody (ACPA) and real-time polymerase chain reaction (PCR) was used to measure the in-vitro effect of AS101 on interleukin (IL)-6 and IL-1β expression in activated primary human fibroblasts. Prophylactic treatment with intraperitoneal AS101 reduced clinical arthritis scores in AIA rats ( P < 0·01). AS101 abrogated the migration of active chronic inflammatory immune cells, particularly VLA-4 + cells, into joint cartilage and synovium, reduced the extent of joint damage and preserved joint architecture. Compared to phosphate-buffered saline (PBS)-treated AIA rats, histopathological inflammatory scores were significantly reduced ( P < 0·05). Furthermore, AS101 resulted in a marked reduction of circulating ACPA in comparison to PBS-treated rats ( P < 0·05). Importantly, AS101 significantly reduced mRNA levels of proinflammatory mediators such as IL-6 ( P < 0·05) and IL-1β ( P < 0·01) in activated primary human fibroblasts. Taken together, we report the first demonstration of the anti-rheumatic/inflammatory activity of AS101 in experimental RA model, thereby supporting an alternative early therapeutic intervention and identifying a promising agent for therapeutic intervention. Graphical Abstract: